2009
DOI: 10.1590/s1676-06032009000400015
|View full text |Cite
|
Sign up to set email alerts
|

Flora vascular não-arbórea de uma floresta de grota na Serra da Mantiqueira, Zona da Mata de Minas Gerais, Brasil

Abstract: A região da Serra Negra constitui um importante remanescente de floresta atlântica situado no sul da Zona da Mata mineira, na Serra da Mantiqueira, composta por um mosaico de campos rupestres (nos afloramentos de quartzito) a arbustais nebulares, florestas estacionais semideciduifólias a perenifólias e florestas nebulares, de ambientes inferomontanos a superomontanos ripícolas a interfluviais. A área de estudo é um fragmento de floresta de grota (floresta perenifólia ripícola), de aproximadamente 0,9 ha, situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“…is an example of a rare bromeliad, which is restricted to 2 places in Minas Gerais State, Brazil, 30 km apart: Ibitipoca State Park, a State conservation unit, and Serra Negra, an unprotected area (Versieux, 2011). Both locations belong to the Mantiqueira Range Complex and are characterized by a steep relief with altitudes ranging from 900 to 1794 m and heterogeneous vegetation composed of a mosaic of rocky fields and forest fragments (Menini et al, 2009). The species can be seen in the rocky landscapes mainly at altitudes higher than 1400 m (Monteiro and Forzza, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…is an example of a rare bromeliad, which is restricted to 2 places in Minas Gerais State, Brazil, 30 km apart: Ibitipoca State Park, a State conservation unit, and Serra Negra, an unprotected area (Versieux, 2011). Both locations belong to the Mantiqueira Range Complex and are characterized by a steep relief with altitudes ranging from 900 to 1794 m and heterogeneous vegetation composed of a mosaic of rocky fields and forest fragments (Menini et al, 2009). The species can be seen in the rocky landscapes mainly at altitudes higher than 1400 m (Monteiro and Forzza, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Carvalho-Silva and Guimarães (2008), Peperomia is predominant in Dense Ombrophilous Forests, and less frequent in Seasonal Forests, in which humidity levels are low, as confirmed by Menini Neto et al (2009b), who found it to be the most representative genus of epiphytes in a Riverine Forest in the Zona da Mata of MG. However, Cervi and Borgo (2007) found Peperomia to be the most representative genus in a fragment of Seasonal Semideciduous Forest, similar to the results of this study.…”
Section: Discussionmentioning
confidence: 89%
“…In general, these families are the five most representative in the epiphytic synusia both in the Atlantic Forest (KERSTEN, 2010) as well as globally (MADISON, 1977), occupying however, a different position to that found in FFS. Orchidaceae is frequently the richest family in studies concerning epiphytic flora in the Neotropical Region, followed by Bromeliaceae (DISLICH; MANTOVANI, 1998; BORGO, 2007;BUZATTO et al, 2008;KERSTEN et al, 2009;MENINI NETO et al, 2009b;GERALDINO et al, 2010), and if Microgramma is cited as the richest genus, it often shares this position with other genera (ROGALSKI; ZANIN, 2003;BREIER, 2005;MANIA;MONTEIRO, 2010). The other recorded genera (Anemia, Polybotrya and Serpocaulon) often have a low or intermediate richness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Serra Negra, localizada na Serra da Mantiqueira, exibe uma fitofisionomia complexa, composta por Campos Rupestres e Florestas Ombrófilas, além de áreas ecotonais. É uma área notavelmente diversa (Menini Neto et al 2009) e conta com o registro, até agora, de pelo menos quatro espécies novas nas famílias Apocynaceae, Lauraceae e Orchidaceae (Batista et al 2008, Assis & Mello-Silva 2010, Matozinhos & Konno 2011 Este trabalho teve por objetivo investigar a diversidade taxonômica das Apocynaceae na Serra Negra, fornecendo descrições detalhadas das espécies, chaves de identificação, e pranchas ilustrativas para o reconhecimento e identificação do grupo.…”
Section: Introductionunclassified